Susceptibility of Some Grapevine Cultivars and Rootstocks to Crown Gall Disease - Mahmoodzadeh, H.; Doulati Baneh, H. (South African Journal of Enology and Viticulture, 2016)
The effects of five interspecific hybrid rootstocks on the susceptibility of grafted scions to crown gall were studied for six years in field as well as greenhouse experiments. The incidence of crown gall on susceptible grape scion cultivars (Vitis vinifera cvs. ‘Thompson seedless’ and ‘Red Sahebi’) was not affected by their grafting onto resistant rootstocks, including NAZ4 (Vitis vinifera cv. ‘Jighjigha’ × Riparia Gloire) and NAZ6 (V. vinifera cv. ‘Gharaozum’ × Kober 5BB), or on self-rooted cultivars when the inoculated vines were monitored over a three-month period in a greenhouse. The weights of the galls induced on non-grafted vines by two of six strains of Agrobacterium vitis and Agrobacterium tumefacience biovar 1 were significantly different. A. vitis strain AG57 and Agrobacterium tumefacience biovar 1 strain 16/6 induced significantly larger galls (8.9 and 5.4 mm respectively) on ‘Thompson seedless’ and ‘Red Sahebi’ when these were growing as self-rooted plants than when grafted on NAZ4 and NAZ6. Observations over a four-year period in the field showed that there was no difference in crown gall incidence until the second year. Scions grafted onto rootstocks of NAZ4 and NAZ6 had a 21.5% and 6.8% incidence, compared to 55% for self-rooted vines. In another field experiment with naturally infected scions of V. vinifera cv. ‘Asgari’ (a very susceptible cultivar), crown gall was apparent on vines grafted onto all rootstocks after six years. The incidence of crown gall was 18% on NAZ6 compared to 68% on NAZ1. During a five-year period, many self-rooted vines died, compared to only a few scions grafted onto NAZ4 and NAZ6 rootstocks that died. At the end of the study, many pathogenic strains of Agrobacterium spp. were isolated from the roots of ‘Thompson seedless’ and ‘Red Sahebi’ vines, but not from roots or vines when NAZ4 and NAZ6 rootstocks were used.